World experience on the diagnosis of interstitial diseases of the lungs in children (up-date 2017) - M.O. Gonchar; O.L. Logvinova (Zaslavsky O.Yu., 2017)
The article presents modern principles of classification, diagnosis and treatment of interstitial lungs diseases in children for the practice of pediatricians, family doctors, pediatric pulmonologists, thoracic surgeons, transplantologists. Interstitial lung diseases are part of the structure of diffuse parenchymal diseases of the lungs, which today includes more than 80 nosological forms. Objective examination, physical development, pulse oximetry, chest radiography, high resolution computed tomography, echocardiography, genetic testing of bronchoalveolar lavage and pulmonary biopsy are important for the diagnosis of interstitial lung disease in a child. A modern algorithm recommended by the American Thoracic Society for the diagnosis of interstitial lung disease in a child depends on the age, family and personal history of diffuse parenchymal lung disease. The article defines differential diagnostic approaches to the detection of diseases from the group of diffuse parenchymal diseases of the lungs.